Серебряный век: поэзия / [под редакцией Н. Розмана] - Розман Н. (Всемирная литература, 2017)
Экземпляры: ф.1 (20170920) / Инвентарный номер: 54270 / Цена: / Сис.шифр: Р2 / Авт.знак: С 32 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)6-5